2018
DOI: 10.22452/ajba.vol11no1.4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cash Conversion Cycle on Profitability: An Insight into the Agriculture and Food Industries in Thailand

Abstract: Manuscript type: Research paper. Research aims: This study investigates the relationship between cash conversion cycle and profitability that exists in the agriculture and food industries in Thailand. It specifically aims to examine the influence of production cycle, cash collection cycle, and cash payment cycle on profitability. In addition, it also aims to measure the influence of control variables such as size and debt ratios have on profitability. Design/ Methodology/ Approach: This study analysed the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
(24 reference statements)
1
6
1
Order By: Relevance
“…The findings are similar to those of Ogunlade, Oseni and Adeyemi (2021) who found that creditors' conversion period (CCP) had no relationship with financial performance. The findings, nevertheless, differed with those of Linh and Mohanlingam (2018) whose study exhibited a favourable correlation between the two. They also differed with those of Le, Vu, Du, and Tran (2018) who found that creditors payment period had a negative effect on financial performance.…”
Section: Effect Of Creditors Payment Period On Financial Performancecontrasting
confidence: 74%
“…The findings are similar to those of Ogunlade, Oseni and Adeyemi (2021) who found that creditors' conversion period (CCP) had no relationship with financial performance. The findings, nevertheless, differed with those of Linh and Mohanlingam (2018) whose study exhibited a favourable correlation between the two. They also differed with those of Le, Vu, Du, and Tran (2018) who found that creditors payment period had a negative effect on financial performance.…”
Section: Effect Of Creditors Payment Period On Financial Performancecontrasting
confidence: 74%
“…Extensive studies have been done to determine the influence of the CCC on the profitability of companies in various manufacturing industries, with diverse findings ranging from negative to positive, and inconsequential to considerable. For instance, the negative significant effects of CCC on corporate profitability have been found by some researchers, such as Chang (2018), Deloof (2003), Garc ıa-Teruel and Mart ınez-Solano (2007), Jakpar et al (2017), Jaworski and Czerwonka (2022), Linh and Mohanlingam (2018), Mmaduka et al (2022), Nwude et al (2018) and Al-Mohareb (2019), while Mandalaputri et al (2021) have found insignificant positive effects. On the contrary, Lin and Lin (2021), Gill et al (2010) and Amahalu and Beatrice O (2017) have found a significant positive impact of the cash cycle on a firm's profitability, while, AL-Zararee et al (2021), Kasozi (2017), Mbathi et al (2021) and Chowdhury et al (2018) have found positive but insignificant impact.…”
Section: Introductionmentioning
confidence: 93%
“…There was no evidence of an association between cash collecting cycle and profitability. [26]. financial performance, which is measured by the net profit margin, return on asset ratio, and return on equity ratio, and the independent variable of cash management, which is evaluated by the cash ratio and operating cash to debt ratio, is shown in the graph above.…”
Section: F1 Cash Conversion Cyclementioning
confidence: 99%